Strategi Peningkatan Kinerja Nelayan dalam Rantai Pasok Ikan Layur melalui Pengembangan Modal Insani di Pelabuhanratu - Herlina Retnowati; Anggraini Sukmawati; Tri Wiji Nurani (Institut Pertanian Bogor, 2014)
The decrease layur fish export in Pelabuhanratu. The roof of the problems are human resources or human capital, performance and supply chain problems. The purpose of this study is formulating the strategy of increasing fisherman performance strategy in ribbon fish supply chain through develop human capital. The increase of fisherman performance is got from the observe activity depth interview with the people who are related to and fishbone chart analized to identify problems which happened in fisherman that cause decreasing fish export and analytical hierarchy process (AHP) is used for the strategy to get a strategy which is suitanable with the fisherman. From the analyze result that we have done with strategy wisdom we are got is increasing training strategy which is adapted with the requirements we hope that it can increase fisherman performance, we hope that the welfare of fisherman will increase.